Government size and trust - Eiji Yamamura (Economics and Econometrics Research Institute (EERI), 2010)
This paper uses individual level data (the Japanese General Social Survey, 2001) to examine how government size influences generalized trust. After controlling for income inequality, population mobility, city size and various individual characteristics, I found: (1) Using all samples, government size is not associated with generalized trust, and (2) After splitting the sample into worker and non-worker samples, government size does not influence generalized trust for non-workers whereas it significantly reduces generalized trust for workers. This suggests that workers, through their work experience, might confront the greater bureaucratic red tape coming from “larger government”, leading to negative externality effects on the trustful relationship in the labor market.
Keywords: D30; Z13; 330; Government size; Generalized trust